The circumcision blues: a case report with literature review - Li, Meng; Lee, Kristen C.; Nakagawa, Thomas A. (International Journal of Contemporary Pediatrics, 2021)
An 11-day-old Caucasian male developed acquired methemoglobinemia as a result of repeated exposure to topical lidocaine/prilocaine cream following a circumcision. Our patient responded well with treatment of a single dose of intravenous (IV) methylene blue. Methemoglobinemia is a rare but well-explained complication of local anesthetics. It is important for providers to prescribe local anesthetics safely to avoid serious complications, especially with neonates who are at higher risk of developing methemoglobinemia.